Duzhong Fang Attenuates the POMC-Derived Neuroinflammation in Parkinsonian Mice - Li L (Dove Medical Press, 2021)
Lili Li,1,* Shanshan Fan,1,* Wenqi Zhang,1 Dongna Li,1 Zhen Yang,1,2 Pengwei Zhuang,1,2 Juan Han,3 Hong Guo,1 Yanjun Zhang1 1State Key Laboratory of Component-based Chinese Medicine, Tianjin University of Traditional Chinese Medicine, Tianjin, 301617, People’s Republic of China; 2School of Chinese Materia Medica, Tianjin University of Traditional Chinese Medicine, Tianjin, 301617, People’s Republic of China; 3College of Traditional Chinese Medicine, Tianjin University of Traditional Chinese Medicine, Tianjin, 301617, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hong Guo; Yanjun ZhangTianjin University of Traditional Chinese Medicine, Tianjin, 301617, People’s Republic of ChinaEmail cacti1983@163.com ; zyjsunye@163.comBackground: Neuroinflammation and microglia reactivity are now recognized to be features of Parkinson’s disease (PD). Thus, microglia phenotype is a potential new target for developing treatments against PD. Duzhong Fang (DZF) is a traditional Chinese medicine (TCM) prescription. The theory of TCM argues that Duzhong Fang, nourishing yin and tonifying yang, may treat PD. However, its modern pharmacological studies and the underlying mechanisms are unclear.Methods: First, MPTP was used to establish a parkinsonian mouse model, and behavioral testing was used to evaluate the locomotor dysfunction. Then, HPLC, immunohistochemical staining, and Western blot assays were performed to evaluate the survival of dopaminergic neurons. Molecular biological and immunofluorescence staining were used to evaluate the neuroinflammation and microglial activation. In addition, RNA-seq transcriptomics was used to analyze differentially expressed genes and verify by RT-PCR.Results: In the present study, we first confirmed that DZF can alleviate neuroinflammation and ameliorate dyskinesia in parkinsonian mice. Then, further studies found that DZF can regulate microglial morphology and reactivity and act on the POMC gene. POMC is an upstream target for regulating inflammation and proinflammatory cytokines, and DZF can directly inhibit the POMC level and restore the homeostatic signature of microglia in parkinsonian mice.Conclusion: This study found that POMC may have a potential role as a therapeutic target for PD. DZF may inhibit neuroinflammation and play an anti-PD effect by down-regulating the expression of POMC.Keywords: Parkinson’s disease, microglia, inflammation, DZF, POMC